36+c=36

Simple and best practice solution for 36+c=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+c=36 equation:



36+c=36
We move all terms to the left:
36+c-(36)=0
We add all the numbers together, and all the variables
c=0

See similar equations:

| -(8+n)=-3(2n-4) | | (x)(x-2)=323 | | -1/2+r=7/2 | | 2/3r+1/2=7/8 | | 5(c-73)=75 | | x/13=5/17 | | 10-2u=-10-6u | | 144+2h=992 | | 36-c=42 | | O=3x-x | | y=6-1+(-2) | | 8x-3-5x=2x | | -4p+23=11 | | 10r-3=9r-6-5 | | 5(2w-3)+10=3w+16 | | 3(7x+5)=2x-9 | | 12+2h=992 | | 6x-2=19=3x | | C=40/3x+20,R=15x | | 3(x+4)=2x-4 | | y+(-14)=-13 | | −1+x=4 | | -6b-3=-2b+9 | | 6=n/4+4 | | 6g+17=71 | | 42c=36 | | -10-5p+9=9-6p | | 36+c=42 | | -10-2s=4s+8 | | -8/3x+1=13/3+2/3x | | x+19=5x+17 | | 82(2x+8)=28(5x-4) |

Equations solver categories